DIRECTIONS OF IMPROVING THE EFFICIENCY OF ENTERPRISE MANAGEMENT - Syniuk , О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article defines that the success of enterprises depends primarily on the efficiency of the enterprises’ management. Directions to improve the efficiency of enterprise management are proposed in the article. They include rational project management; use of the theory of constraints, i.e. identification and management of the main constraints in the enterprise's activity; change management, i.e. flexibility and adaptability to changes in the internal and external environment; cost reduction, i.e. constant analysis and optimization of costs; modernization and automation of business processes, i.e. implementation of the latest technologies and automation systems; search for new ways of organizing enterprise management; proper marketing, i.e. understanding consumer needs, developing effective marketing strategies and promoting products on the market; employee motivation; more powers to local managers: delegation of authorities and distribution of responsibilities between managers at different levels of the organizational structure; attraction of investors; increasing the loyalty and efficiency of employees. To achieve high efficiency of enterprise management, it is important to adopt complex management changes in various spheres of activity. This can include modernizing production, focusing on marketing and sales, supporting and motivating employees, improving the management system at all levels, attracting external resources and ensuring openness and transparency in communication with the team. The research shows that the success of an enterprise directly depends on its effective management. The proposed directions for improving management efficiency take into account various aspects of the company's activity and are aimed at achieving optimal results in all areas. The implementation of these measures will help to increase the efficiency of the enterprise and ensure its sustainable development at the market.